México, el voto por la democracia - Aguilar, Luis F.; Argüelles, Antonio.; Villa Aguilera, Manuel. (Libros de Textos para el cambio., 1994)
"Collection of essays, some written by Mexico's leading analysts, explores Mexican electoral politics during the 1990s. Topics include the impact of violence, NGOs, public opinion polls, reforms within the PRI, and the electoral process itself. Very useful election data from 1988-94"--Handbook of Latin American Studies, v. 57.